Relevance of donor-specific HLA antibodies in hematopoietic cell transplantation - Tran, Thuong Hien; Heinold, Andreas; Spackova, Magdalena; Pham, Lien; Stelljes, Matthias; Dreger, Peter (Best practice & research, 2024)
Advances in hematopoietic cell transplantation have expanded the use of alternative donors such as haploidentical family donors or mismatched unrelated donors. However, donor-specific HLA antibodies (DSA) have been recognized as a significant risk factor of primary graft failure after HLA incompatible transplantation. Therefore, screening for HLA antibodies and taking DSA into consideration in the process of donor search play an increasingly important role in donor selection. If an HLA compatible donor is not available, desensitization may enable a successful transplantation. In this review, we describe the currently most widely used methods for HLA antibody detections including their pitfalls. In addition, we summarize the results of the studies on the impact of preformed DSA on transplant outcomes and their treatment options. Many more and larger studies are needed to clarify laboratory issues as well as immunological and clinical aspects in the management of DSA.